2019
DOI: 10.3389/fphar.2019.00520
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Factors Affecting Asthma Treatment Response. Potential Implications for Drug Therapy

Abstract: Asthma is a frequent disease, mainly characterized by airway inflammation, in which drug therapy is crucial in its management. The potential of pharmacogenomics testing in asthma therapy has been, to date, little explored. In this review, we discuss pharmacogenetic factors affecting asthma treatment, both related to drugs used as controller medications for regular maintenance, such as inhaled corticosteroids, anti-leukotriene agents, long-acting beta-agonists, and the new biologic agents used to treat severe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 121 publications
(148 reference statements)
1
28
0
2
Order By: Relevance
“…32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA). 13,[16][17][18] Additionally, other candidate genes have been related for the first time to this phenotype in children (SPATS2L, ASB3, IL1RL1, MMP9, and COL2A1). Although several findings support previous evidence of some of these genes in asthma treatment response, inconsistent results across the literature or even across the studies included in this review have been found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA). 13,[16][17][18] Additionally, other candidate genes have been related for the first time to this phenotype in children (SPATS2L, ASB3, IL1RL1, MMP9, and COL2A1). Although several findings support previous evidence of some of these genes in asthma treatment response, inconsistent results across the literature or even across the studies included in this review have been found.…”
Section: Discussionmentioning
confidence: 99%
“…ADRB2 gene has been the most studied candidate gene of SABA response. 16,18,23 It encodes the β 2 adrenergic receptor, which is implicated in the bronchodilation process and is the biological target of β 2 adrenergic agonists. 19 In fact, in the reviewed period four candidate-gene studies have assessed the effect of the SNPs rs1042713 (arginine to glycine [Arg16Gly]) and rs1042714 (glutamic acid to glutamine [Glu27Gln]) on changes in lung function after SABA administration in European 24,25 and Egyptian 26,27 populations (Table 1).…”
Section: Candidate-gene Studies Of Saba Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In the last year, the role of different omics in asthma treatment response has been recapitulated in different reviews [16][17][18][19][20][21]. This review aims to provide an update on the latest findings in omic studies of pediatric asthma treatment response.…”
Section: Introductionmentioning
confidence: 99%